Effects of different intensities of pressure stimulation of an acupuncture point onthe excitability of spinal nerve function - Tachibana, Hina; Chiyo, Hinata; Tani, Makiko; Katsuragi, Hibiki; Mori, Kenta; Suzuki, Toshiaki; Fukumoto, Yuki; Todo, Marina (Journal of Kansai Physical Therapy, 2023)
In this study, we clarified the effects of differences in pressure stimulation intensity of an acupuncture pointon spinal motor nerve function, and examined whether Acupoint Stimulation Physical Therapy (ASPT) is effective in the absence of pain. In 20 healthy subjects (mean age: 20.29 years), ASPT was performed on Chize (LU5) on the lunar lung sutra, and F waves arising in the muscle groups on the ball of the thumb on the non-dominant hand were measured at rest before the ASPT trial, during the ASPT trial, and 0 min, 5 min, 10 min, and 15 min after the ASPT trial. The pressure stimulation intensity of the ASPT trial was set at two painthresholds, 100% and 50%. The results show that the amplitude of the F/M ratio was significantly reduced at 5, 10, and 15 minutes after the ASPT trial compared to during the ASPT trial at 100% intensity pressure stimulation, but there was no difference at the 50% intensity pressure stimulation. These results suggest that pressure stimulation with a pain threshold of 50% is unlikely to have an inhibitory effect immediately after stimulation. Therefore, the intensity of pressure stimulation of acupuncture points in clinical practice should be performed at the pain threshold level for the immediate suppression of the excitability of spinal motor nerve function.